2020
DOI: 10.1177/0956462419890737
|View full text |Cite
|
Sign up to set email alerts
|

Mycoplasma genitalium and antimicrobial resistance in Europe: a comprehensive review

Abstract: Antibiotic resistance in Mycoplasma genitalium has been emerging in Europe. Also, discrepancies on the management and treatment of sexually transmitted infections may have distinctly influenced the prevalence of antimicrobial resistance among European countries. This comprehensive review of the literature published between 2012 and 2018 updates antimicrobial resistance data in M. genitalium in Europe. Overall, macrolide resistance is rapidly increasing in this region, where many countries are exceeding 50%. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
39
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 42 publications
0
39
2
2
Order By: Relevance
“…The authors of other studies have suggested that a syndromic approach (ie, management of a patient whereby a syndrome is used as a basis for the treatment of the causative organisms) and the use of a single dose of azithromycin for treatment of NG (as part of dual therapy), non-gonococcal urethritis/non-specific genital tract infection, or known MG infection contribute to the emergence of macrolide resistance in MG, because this regimen is suboptimal and might exert selective pressure on resistant strains. 28,29,31 A similar phenomenon has been observed with respect to FQ, especially in Japan, where frequent use of the second-line antibiotic sitafloxacin caused selection of resistant strains, leading to high rates of FQ resistance in MG.3 In public clinics in Hong Kong, a single dose of azithromycin or a 1-week course of doxycycline is used as empirical treatment for non-gonococcal urethritis or non-specific genital tract infection. If no culprit pathogen is identified and the patient complains of persistent symptoms during follow-up, a 1-week course of moxifloxacin for possible MG is considered, following exclusion of other causes (eg, non-compliance).…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…The authors of other studies have suggested that a syndromic approach (ie, management of a patient whereby a syndrome is used as a basis for the treatment of the causative organisms) and the use of a single dose of azithromycin for treatment of NG (as part of dual therapy), non-gonococcal urethritis/non-specific genital tract infection, or known MG infection contribute to the emergence of macrolide resistance in MG, because this regimen is suboptimal and might exert selective pressure on resistant strains. 28,29,31 A similar phenomenon has been observed with respect to FQ, especially in Japan, where frequent use of the second-line antibiotic sitafloxacin caused selection of resistant strains, leading to high rates of FQ resistance in MG.3 In public clinics in Hong Kong, a single dose of azithromycin or a 1-week course of doxycycline is used as empirical treatment for non-gonococcal urethritis or non-specific genital tract infection. If no culprit pathogen is identified and the patient complains of persistent symptoms during follow-up, a 1-week course of moxifloxacin for possible MG is considered, following exclusion of other causes (eg, non-compliance).…”
Section: Discussionmentioning
confidence: 72%
“…Although the populations have differed among studies, similarly high rates of macrolide resistance (Table 4). 3,[23][24][25][26][27][28] Several studies also demonstrated consistent increases in resistance rates over time. 3,28,29 All mutations detected in this study have been described previously; while C184T (Pro62Ser) in parC is of unknown significance, others are known to confer antibiotic resistance leading to higher minimal inhibitory concentrations and treatment failure.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…The appreciation that N. gonorrhoeae is asymptomatic for much or most of the time it circulates in a population means that antibiotics used for other indications needed to be considered (bystander selection) [4]. Since, gonococcal infections cluster with other STIs, a widely held formulation of this view was that the bystander selection was predominantly confined to antibiotics used to treat other STIs (termed the STI bystander theory) [5].…”
Section: Introductionmentioning
confidence: 99%